Processing Speed Weakness in Children and Adolescents with Non-Hyperactive but Inattentive ADHD (ADD) - Goth-Owens, Timothy L. (2010)
DSM-IV-TR defines ADHD-Predominantly Inattentive as allowing up to five symptoms of hyperactivity/impulsivity, while theories of the inattentive type usually assume a group that is hypoactive and characterized by processing speed and cognitive interference deficits. In a community-recruited sample of 572 children and adolescents, a pure inattentive subtype of ADHD (ADD) was defined as those who met DSM-IV-TR criteria for ADHD-PI but had two or fewer hyperactive/impulsive symptoms. Processing and output speeds of those with ADD were compared to those identified with DSM-IV-TR ADHD combined type and non-ADHD controls. These results were then contrasted with those found when DSM-IV-TR defined ADHD-PI was compared with ADHD-C and controls. Processing and output speed were assessed with the Trailmaking A and B and the Stroop Naming Tests. Cognitive interference control was assessed with the interference score from the Stroop Task. Slower cognitive interference speed was found in the ADD vs. ADHD-C and controls comparisons, but not the ADHD-PI versus ADHD-C and controls comparisons. On output speed measures, ADD exhibited the slowest performance, significantly different from controls and the effect size for the set-shifting speed contrast (Trailmaking B) contrast was double that of the ADHD-PI vs. control comparison. ADHD-Inattentive type as defined by the DSM-IV-TR is a heterogeneous condition with a meaningful proportion of those affected exhibiting virtually no hyperactive/impulsive symptoms. This subgroup may represent a distinct inattentive condition characterized by poor cognitive interference control and slow processing or output speed.